2017
DOI: 10.1093/bib/bbx132
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of protein–protein interactions between fungus (Magnaporthe grisea) and rice (Oryza sativa L.)

Abstract: Rice blast disease caused by the fungus Magnaporthe grisea (M. grisea) is one of the most serious diseases for the cultivated rice Oryza sativa (O. sativa). A key factor causing rice blast disease and defense might be protein-protein interactions (PPIs) between rice and fungus. In this research, we have developed a computational pipeline to predict PPIs between blast fungus and rice. After cross-prediction by interolog-based and domain-based method, we achieved 532 potential PPIs between 27 fungus proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Of the predicted PPIs, only 29.9% (604) of interactions were supported with the evidences of sequence similarity and interacting domain pairs. Moreover, we found that 17 predicted PPIs could be identified by the previous study with the sequence-based method (Ma et al, 2019). These results indicated that the structure-based method could efficiently discover new rice-blast fungus PPIs beyond those interactions inferred from sequence similarity.…”
Section: Proteome-wide Prediction Of Ppis Between Rice and Blast Fungusmentioning
confidence: 63%
See 1 more Smart Citation
“…Of the predicted PPIs, only 29.9% (604) of interactions were supported with the evidences of sequence similarity and interacting domain pairs. Moreover, we found that 17 predicted PPIs could be identified by the previous study with the sequence-based method (Ma et al, 2019). These results indicated that the structure-based method could efficiently discover new rice-blast fungus PPIs beyond those interactions inferred from sequence similarity.…”
Section: Proteome-wide Prediction Of Ppis Between Rice and Blast Fungusmentioning
confidence: 63%
“…Over 70% of PPIs between rice and blast fungus were inferred from structural similarity, which greatly expanded the landscape of the rice-blast fungus PPI network. Compared with the previous PPI network, 17 of PPIs were identified by the structure-based method (Ma et al, 2019). Although the number of common PPIs was relatively small, the results were significantly overlapped between the two independent studies (i.e., Fisher's exact test p < 5.6e-39).…”
Section: Discussionmentioning
confidence: 87%
“…Remmele and co-workers used interolog mapping to identify host-pathogen interactions of A. fumigatus during human and mouse infection, highlighting the roles of the PLB1 virulence factor and APP anti-fungal host protein [213]. Several network studies have also investigated yeast infection in plants [61,89,91,[214][215][216][217].…”
Section: Integrationmentioning
confidence: 99%
“…On the other hand, the lack on PPIs knowledge about plant organisms is driving many biologists to reconstruct PPI networks experimentally ( Table 2 ). Of note, a number of studies and databases ( Table 3 ) focus on host-pathogen PPI, suggesting that this field of PPIs is of great interest to improve strategies oriented to manage destructive pathogens that cause huge crop losses every year worldwide [ 35 , 184 , 185 , 188 , 189 , 190 ].…”
Section: Co-expression and Ppi Network As Models To Investigate Pmentioning
confidence: 99%